Study on the main oilseed production, processing and storage capacities in Romania - Marin Ancuța (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The purpose of the work is to analyze the main production, processing and storage capacities of rapeseed, sunflower and soybean boxes in Romania, starting from general information such as cultivated areas, productions, the number and capacity of storage spaces, the analysis is based on statistical data from the period 2013-2022 collected from INS and MADR. Considering their wide use, it is opportune to analyze them based on the bibliometric, bibliographic, statistical-mathematical data analysis and the cause-effect diagram. The analysis showed that the county with the largest area cultivated with sunflowers is Dolj, with Cæalæara÷si rape and Bræaila soybeans, the calculated yields being 2,725 tons/ha for sunflower, 3,022.89 tons/ha for rape and 3,422 tons /ha for soybeans. In the pessimistic scenario, the forecasted productions for the period 2023-2026 for sunflower could vary between 1,937-2,089 thousand tons, and in the optimistic one between 3,866-4,018 thousand tons. For rapeseed, in the pessimistic scenario, the predicted productions for the period 2023-2026 could vary between 331-450 thousand tons, and in the optimistic one between 1,946-2,166 thousand tons. For soybeans in the pessimistic scenario, the forecasted productions for the period 2023-2026 could vary between 74-130 thousand tons, and in the optimistic scenario between 415-535 thousand tons. Knowing the production potential for oilseeds in irrigated and non-irrigated systems, we appreciate that the forecast values are plausible, considering that the forecast was made taking into account the calculated multi-year averages.
Keywords: Q10; Q15; 330; sunflower; rapeseed; soybean; processing; storage